Lower CALLY index levels indicate higher poor functional outcome risk in acute ischemic stroke patients treated with endovascular thrombectomy - Lu, Yunnan; Zhu, Xiaohua; Xu, Yaojia; Li, Yongxin; Dai, Qingyong; Chang, Xia (Frontiers in Aging Neuroscience, 2025)
BackgroundThe imbalance in the nutrition-immunity-inflammation status is linked to the prognosis of various diseases. This study sought to evaluate the correlation between the C-reactive protein-albumin-lymphocyte (CALLY) index and the outcomes of acute ischemic stroke (AIS) managed with endovascular thrombectomy (EVT).MethodsThis study retrospectively enrolled 473 AIS patients who underwent EVT from a multicenter investigation. Poor functional outcome was defined as a modified Rankin scale score exceeding 2 points at 90 days after EVT. The cutoff value for the CALLY index was determined using the receiver operating characteristic curve. Multivariable logistic regression models were utilized to explore the association between the CALLY index and poor functional outcome and restricted cubic splines was used to illustrate the relationship between the CALLY index and the risk of poor functional outcome after EVT.ResultsPoor functional outcomes occurred in 214 (45.2%) patients at 90 days after EVT. The cutoff for the CALLY index was 10^ (−0.635). Multivariate logistic regression revealed that the CALLY index was significantly associated with poor functional outcome (odds ratio [OR]: 0.80, 95% confidence interval [CI]: 0.70–0.91, p < 0.001; high versus low OR: 0.64, 95% CI: 0.41–1.00, p = 0.048). The restricted cubic spline analysis indicated an inverse association between the CALLY index and the risk of poor functional outcome (P for nonlinearity = 0.373).ConclusionOur study identified that a lower CALLY index is an independent predictor of poor functional outcome after EVT. The CALLY index could emerge as a practical, cost-effective, and promising predictive biomarker for adverse outcomes in AIS patients undergoing EVT treatment.